เงื่อนไขทางด้านลิขสิทธิ์ กระบวนการผลิต และกลยุทธ์การตลาด ของนิตยสารเนชั่นแนล จีโอกราฟฟิก ฉบับภาษาไทย - บุญญารัตน์ มีฮิ่น (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study conditions of licensing, production process and marketing strategies of a licensed magazine, National Geographic (Thai edition). The methodology used is an in-depth interview and a study of the magazine’s contents and related documents. The finding shows that, regarding the licensing, National Geographic Society, which owns the copyright and license of the magazine, has strict conditions on licensing. Before the license was granted, it had evaluated the potential of the licensee, or Amarin Printing and Publishing Public Company Limited in this case, in order to ascertain whether or not the licensee can meet the high standard of the international publication. After an official license, the licensee must strictly follow the entailed rules in order to maintain the quality and the legacy of this 122 year magazine. Such strict rules dictate the production process of the Thai Edition, including quality of writing, layout, and printing. The Thai editorial department monitors accuracy of contents and quality of the final print. The licensor randomly monitors the quality of the published copies on a yearly basis - by employing Thai readers in the USA to provide feedbacks. Regarding marketing strategies, the Thai Edition relies on integrated marketing tactics suitable for the target audience. A website is another channel for interested readers to follow a monthly synopsis of the magazine, download photos and register for a subscription. It is expected that the website will play a more important role for communication between editorial teams and readers - thanks to its fast accessibility and low costs.